EFFECT OF OBESITY ON PULMONARY FUNCTION - NIBEDITA PRIYADARSINI; DIPTI MOHAPATRA; MANASI BEHERA (International Journal of Pharma and Bio Sciences, 2014)
The magnitude of the increasing obesity prevalence has become important health problem. The present study was done to correlate obesity with respiratory function in a group of Indian population. A total of 99 cases between age group 15-45 years of both sexes were taken with no history of asthma or any respiratory diseases. Their height, weight, BMI were measured. The persons having BMI 18.5-22.99 were taken as control group for age and sex. The persons with BMI 25kg/m² to 40kg/m² were taken as study(obese) group. Then Spirometry (both static & dynamic lung volumes) was performed in all subjects. FVC, FEV1, FEV1/FVC, ERV, MVV were used as measures of ventilatory function. FVC, FEV1, ERV & MVV were decreased in obese group. These results indicate that obesity had negative correlation with pulmonary function.